Kebijakan Hukum dalam Upaya Penanggulangan Tindak Pidana Kecelakaan Lalu Lintas yang Mengakibatkan Matinya Korban - Dahnial Saragih; Taufik Siregar; Rizkan Zulyadi (Mahesa Research Center, 2021)
Traffic problems are one of the problems on a national scale that develop in tune with the development of society. The problem faced today is the high number of traffic accidents on the highway. This study aims to determine the accountability and legal policies in an effort to overcome the perpetrators of traffic accidents that resulted in the death of the victim at the Humbang Hasundutan Police Traffic Unit. The research method used is normative or doctrinal juridical legal research as library research or document study, which has descriptive analysis. The results of the study indicate that the law against perpetrators of traffic accidents resulting in the death of the victim is regulated in Article 359 of the Criminal Code, Article 106 paragraph (2), Article 229, Article 310 paragraphs 1 to 4 and Article 312 of the Law. No. 22 of 2009 concerning Road Traffic and Transportation and Government Regulation Number 37 of 2017 concerning Traffic and Road Transportation Safety. Legal policy in an effort to overcome the crime of traffic accidents that resulted in the death of the victim at the Humbang Hasundutan Sat.Lantas Police carried out penal and non-penal where accountability is carried out by applying imprisonment as regulated in Article 310 paragraph (4) of Law no. 22 of 2009 concerning Road Traffic and Transportation.